First-Principles Study of Pt-Based Bifunctional Oxygen Evolution & Reduction Electrocatalyst: Interplay of Strain and Ligand Effects - Seung-hoon Kim; Yoonmook Kang; Hyung Chul Ham (Energies, 2021)
We examined the oxygen evolution reaction (OER) and oxygen reduction reaction (ORR) of Pt-based Pt3M/Pt nanoalloy catalysts (where M represents a 3d transition metal) for bifunctional electrocatalysts using spin-polarized density functional theory calculations. First, the stability of the Pt3M/Pt catalyst was investigated by calculating the bulk formation energy and surface separation energy. Using the calculated adsorption energies for the OER/ORR intermediates in the modeled catalysts, we predicted the OER/ORR overpotentials and potential limiting steps for each catalyst. The origins of the enhanced catalytic reactivity in Pt3M/Pt catalysts caused by strain and ligand effects are explained separately. In addition, compared to Pt(111), the OER and ORR activities in a Pt3Ni/Ptskin catalyst with a Pt skin layer were increased by 13.7% and 18.4%, respectively, due to the strain and ligand effects. It was confirmed that compressive strain and ligand effects are key factors in improving the catalytic performance of OER/ORR bifunctional catalysts.